SERUM PROGESTERONE AND OVULATION TIME IN COWS PRESENTED FOR AI AND THE SUBSEQUENT PREGNANCY RATE - EZHILARASAN, C; MURUGAVEL, K; ANTOINE, D; RAJU, MS (The Indian Journal of Animal Reproduction, 2022)
Serum progesterone at the time of AI, ovulation time and the subsequent pregnancy rate was investigated in 68 crossbred Jersey cows presented for AI (day 0). Ovarian ultrasonography was carried out, a) to record preovulatory follicle (POF) on day 0, b) disappearance of POF on day 1 or day 2 after artificial insemination (AI), c) to confirm ovulation on day 12 post-AI, and d) on day 27 to confirm pregnancy. Serum progesterone was estimated from the blood samples collected on day 0. Ovulation rate in cows was 91.2% (n=62/68). Out of these, the percentage of cow that ovulated between 0-24h (67.6%) was higher (p<0.05) than their counterparts ovulating between 24-48h (11.8%). The number of cows ovulating before AI and 48h after AI was three and five, respectively. The percentage of anovulation was 8.8. Pregnancy rate for the cows that ovulated between 0-24h or between 24-48h after AI was 54.3% and 75.0%, respectively. Serum progesterone was higher (p<0.05) in cows that ovulated before AI, >48h after first AI and in the anovulatory cows compared to their counterparts ovulating between 0-24h and 24-48h following first AI, thus concluding that 20.6% cows reported for AI were not in proper estrus.